Public Administration and Local Government Role in Tourism Developpement - Mοstafa ABAKΟUY; Rοua LAMRANI (Communications of International Proceedings, 2025)
The motive behind the study The motive behind the study is to approach the relationship between the role of public administration and tourism development. The aim is to define the potential influencing factors that contribute to this development. The gap in literature that makes this study important At the operational level, several initiatives are being implemented to promote tourism development in Morocco, notably through the creation of territorial competence centers, the establishment of platforms for the exchange and sharing of territorial data, the training of local stakeholders in territorial intelligence tools, and the promotion of innovative projects at the local level seems to be insufisant. The methodology used in the study Methodologically we adopted a qualitative approach using NVivo software through semi-structured interviews with managers of the organization under study. We supplemented our work with an exploratory study, observing the role of public administration. Summary of the findings We observed through the study that governance, stakeholder involvement, financial incentives, relational mechanisms and stakeholder networks, the profile of the manager, their skills, training and qualifications, government initiatives, regulations specific to the tourism sector, and technological advances are factors in tourism development.
Keywords: Public administration; tourism developement; governance.